THE END OF THE HONEYMOON: PENAL DISCOURSE AND THE HUMAN RIGHTS OF PRISONERS IN THE AFTERMATH OF SOUTH AFRICA’S SECOND DEMOCRATIC ELECTION ‒ PART TWO - Stephen Allister Peté (Obiter, 2017)
The years immediately following South Africa’s second democratic election, held in June 1999, were significant in that they marked the end of the “honeymoon” period which followed the country’s transition from apartheid to democracy in 1994. This article focuses on the public discourse surrounding imprisonment in South Africa during this important “post-honeymoon” period. The article traces the continued systematic violation of the basic human rights of many of those confined in South African prisons throughout the period. Part One of the article dealt with the many public debates surrounding chronic prison overcrowding and its effects, whereas Part Two deals with a host of evils which beset the South African penal system at this time, including very poor conditions of detention, high levels of gang activity, the spread of HIV/AIDS, the escape of dangerous criminals from different prisons in the country, and instances of corruption and other criminal activity amongst prisoners and staff.